Advances in interdisciplinary practice in industrial design : proceedings of the AHFE 2018 International Conference on Interdisciplinary Practice in Industrial Design, July 21-25, 2018, Loews Sapphire Falls Resort at Universal Studios, Orlando, Florida, USA /: proceedings of the AHFE 2018 International Conference on Interdisciplinary Practice in Industrial Design, July 21-25, 2018, Loews Sapphire Falls Resort at Universal Studios, Orlando, Florida, USA. ([2018]) - Unknown
No abstract available